Tingkat Kepuasan Masyarakat dalam Pengurusan Perizinan SIUP Agribisnis di Badan Pelayanan Perijinan Terpadu Satu Pintu dan Penanaman Modal Kota Denpasar - L. Mira Ambarasari Saka; IM. Narka Tenaya; IM. Sudarma (JURNAL MANAJEMEN AGRIBISNIS, 2014)
The primary function of government is to serve the public. To increase   the public satisfaction is one of the efforts to improve the quality of public services. The service of trade business license (SIUP) for investing agriculture activities (agribusiness)   is one of  licensing  service types  that organized by BPPTSP and PM Of the  Denpasar   Municipality . The purpose of this study was to analyze the role of variables between the behavior of services and service standards to the satisfaction levels of public and influence the level of people's satisfaction with the use of an agency  service in  processing Agribusiness trade  license (SIUP ) in BPPTSP and PM of  the  Denpasar Municipality. The number of samples was determined by 90 respondents who have had SIUP with agribusiness activity period of 2010 s/d 2013. Data Technical Analysis used Partial Least Square (PLS) with the Smart PLS program. The results showed that the behavior of the service variables have a correlation coefficient (r) of 0.956 with the value of the contribution (R2) greater than 0.914 standard variable satisfaction level of service to the public, showed a correlation coefficient (r) of 0.930 with the value of the contribution (R2) 0.865. Based on the result of R2 values, it means the better behavior of the service makes the higher  level of public  satisfaction. The good quality of service behavior will give an impact on the quality of service satisfaction. The  Good quality  of service behavior in BPPTSP and PM  of  Denpasar  municipality will increase public satisfaction and  encourage the Applicants  to submit SIUP agribusiness independently. The level of public  satisfaction proved positive and significant effect on service bureau services. It shown by the path parameter coefficients positive value of 0.859 with a  statistic of 24.879 (t-statistic> 2.58), so that the level of public  satisfaction has  positive influence on the use of service bureaus in BPPTSP and PM  of  Denpasar  municipality. The conclusion is  although  the public satisfaction in good  level of  service behavior  but  in reality the communities still using bureau services for helping to submit of  agribusiness trade license . It caused  the use of agency services are considered more practical.